Workplace psychosocial stressors experienced by migrant workers in Australia: A cross-sectional study - Milner, A.; Reid, Alison; Daly, A.; Carey, Renee; Darcey, E.; Chih, Hui Jun; LaMontagne, A. (Public Library of Science, 2018)
Objective: To explore work-related psychosocial stressors among people of Chinese, Vietnamese and Arabic-speaking backgrounds currently working in Australia. Methods: In 2015, a telephone survey of 585 Vietnamese, Chinese and Arabic-speaking workers asked about workplace bullying, ethnic discrimination, job complexity, degree of control, security and fairness of payment along with demographic and employment information. Estimates of job-related psychosocial stressors were derived and regression analyses used to identify significant associations. Results: At least one workplace stressor was reported by 83% of the workers in the study. Education was significantly associated with experiencing any psychosocial stressor and also with the total number of stressors. Workers aged 45 years and older were more likely to be bullied or experience racial discrimination compared with younger workers of any ethnicity. There was a greater likelihood of reporting low control over a job when the interview was conducted in a language other than English and the workers were either Chinese or Arabic. Workers on a fixed-term contract, independent of ethnicity were more likely to report a job with low security. Overall psychosocial job quality decreased with education and was associated with occupation type which interacted with ethnicity and gender. Conclusions: The results suggest that job-related psychosocial stressors are widespread but not uniform across ethnic groups. Further research into what drives differences in work experience for migrant groups would provide information to guide both employers and migrants in ways to reduce workplace psychosocial stressors.